Perceptions of government stakeholders on ageing and assisted care in the Cape Coast Municipal Area - Aboh, Irene (Advances in Social Sciences Research Journal, 2020)
Aim: To explore the perceptions of government stakeholders on assisted care for the aged in a Metropolis, in Ghana. Method: This is a qualitative sub-study of a larger study on developing a model for the care of the aged in the Cape Coast Metropolitan area. The following questions were put to the key informants: Have you noticed an increase in the number of the aged in the communities? What are government plans for the aged? How is the welfare and the caring from traditional attention, what is your view on the introduction of assisted care in Ghana? Data was collected through key-informant in-depth interviews with 10 government stakeholders directly in charge of policy implementation in the metropolis. Data collection took place over a period of four months from October 2016 to January 2107. The interviews were digitally recorded and transcribed verbatim, coded and analyzed. Findings: There were no preparations made for ageing, the government had plans and strategies for aged care. Traditional caring provision is inadequate and the concept of assisted living is regarded with mixed feelings. Some informant described assisted caring as an unaccepted practise that should not be encouraged. Conclusion: Those implementing the policies are not certain of the feasibility of the programme. Awareness of assisted living should be promoted so that the community can make their own decisions.